Lilith negra : Símbolos culturais em um debate intersemiótico - Rocha, Francisca Raquel Queiroz Alves (2018)
The purpose of this dissertation is to show an analytical and introductory study about the character Lilith, through the evolution of the meaning that has attributed her history present in the religion traditions, and how occurred the apropriation and exploration of this symbol in the literary work called Xenogenesis of the afro-american's writer Octavia Estelle Butler, as an Inter-Semiotic object of the cultural, social and religious relations that cover our society. For this, we will glimpse through an eschatological myth of how the apocalypse happened on Earth, as those who survived had the oportunity to see a cosmogonic rebirth of the new Genesis, of the chaos until the cosmos. And that genesis is always linked to the assumptions that involve the sexuality, way by which it will be present or evidenced in the mythological narratives that involve the Lilith's name, and consequently will be reaffirmed in the Octavia's literary work. The Lilith and the sexuality will be explained while compairing through an intersemiotic dialogue, the constructive, deconstructive and reconstructive elements linked to the character present in the religious, mythological and literary universe, object of this dissertation.